Optimal probe length varies for targets with high sequence variation: Implications for probe library design for resequencing highly variable genes - Haslam, N.J.; Whiteford, N.E.; Weber, G.; Prügel-Bennett, A.; Essex, J.W.; Neylon, Cameron (PUBLIC LIBRARY SCIENCE, 2008)
© 2008 Haslam et al.